THE EFFECT OF RISK MANAGEMENT COMMITTEE ON THE FINANCIAL PERFORMANCE OF LISTED DEPOSIT MONEY BANKS IN NIGERIA - Blessing Unekuojo Oguche; Luka Mailafia; Aliyu Abdullahi AHMED (Gusau Journal of Accounting and Finance)
This study examined the effect of risk management committee on the financial performance of listed Deposit Money Banks (DMBs) in Nigeria. Financial performance which is the dependent variable was proxied by return on assets (ROA), while enterprise risk management as the independent variable was proxied by risk management committee independence, risk committee size, ISO 27001 framework and COSO framework. Data were collected from secondary source. The data were extracted from the audited annual reports of the 14 listed DMBs on the Nigerian Exchange (NGX) for the period of 2016-2022. The study employed the Generalized Least Square (GLS) regression technique in analyzing the study data. The findings revealed that ISO 27001 framework and COSO framework have a positive and significant effect on the financial performance of listed DMBs in Nigeria. Hence, it was concluded that ISO 27001 framework and COSO framework are among the major determinants of financial performance of listed DMBs in Nigeria. It was recommended that the managements of the listed DMBs in Nigeria should increase the use of ISO 27001 and COSO framework to assist them in mitigating risk and increasing the financial performance of the banks.